Predictions of short-term rates and the expectations hypothesis of the term structure of interest rates - Massimo Guidolin; Daniel L. Thornton (European Central Bank (ECB), 2008)
Despite its important role in monetary policy and finance, the expectations hypothesis (EH) of the term structure of interest rates has received virtually no empirical support. The empirical failure of the EH was attributed to a variety of econometric biases associated with the single-equation models used to test it; however, none account for it. This paper analyzes the EH by focusing on its fundamental tenet - the predictability of the short-term rate. This is done by comparing h-month ahead forecasts for the 1- and 3-month Treasury yields implied by the EH with the forecasts from random-walk, Diebold and Lei (2006), and Duffee (2002) models. The evidence suggests that the failure of the EH is likely a consequence of market participants' inability to predict the short-term rate.
Keywords: E40; E52; 330; expectations theory; random walk; time-varying risk premium; Erwartungsbildung; Random Walk; Zinsstruktur; Theorie